Commodity associations and their potential role in supply chain development - Shepherd, A.W.; Cadilhon, J-J. (2008)
Commodity associations are organizations that bring together a wide spectrum of interest groups related to a particular commodity or sector in a particular country, whether for export, for the domestic market, or for both. Such associations can have, as members, individual farmers or their associations, crop buyers, processors, distributors, and exporters, as well as suppliers of support services and, sometimes, government representatives. Drawing on a literature review and case studies of relevant associations in Ghana, Mali, Nepal, the Philippines, South Africa, Vietnam, and Zimbabwe and covering the meat, poultry, horticulture, coconut, and rice sectors, this paper explores the role of such associations in improving supply chain performance. Particular attention is paid to interprofessional associations, a concept first developed in France, which draw their membership from associations representing each activity or " profession" of the chain. Associations can play a particularly important role as a focal point for policy dialogue with government, but they also have many other functions. These include regulation, setting or advising on grades and standards and their implementation, promotion of trademarks or quality signs within the industry, support for research, export and domestic market promotion, provision of information and statistics, education and training, and support to government in trade negotiation. Representing all sectors of an industry, such associations also have a potential dispute-resolution role. In many countries, policy formulation is inadequate because there are no clear channels through which governments can approach the private sector. Inefficiencies also exist within commodity sectors because of the lack of communication between chain actors. The paper concludes that the need to address such weaknesses, combined with the positive role played by many existing associations, argues for further development of the concept in developing countries. However, developmental efforts must consider the need to promote sustainable organizations.
Keywords: Supply chains; Commodity associations; Interprofessional associations